A multilevel perspective on organizational buying behavior in coopetition–an exploratory case study. Issue 3 (June 2017) - Rajala, Anni; Tidström, Annika
Abstract: This article offers a new and interesting perspective on organizational buying behavior by focusing on the simultaneous existence of both cooperation and competition, that is, coopetition. Coopetition may bring undesired knowledge leaks, opportunism, and weakened competitive advantage, and it is therefore important to understand how coopetition develops over time through interrelated activities on multiple levels. The article aims to improve our understanding of the development of organizational buying behavior through adopting a multilevel perspective on coopetition. The empirical study is based on exploratory case study research involving a single case from the manufacturing sector featuring a large multinational buyer and its supplier. The findings of the study show that organizational buying behavior in coopetition develops through interrelated activities on the individual, the organizational, and the relational level. Over time, dominating activities evolve from being ambivalent on an individual level to become authoritative on a company level and finally to being opportunistic on a relational level. Theoretically, this study contributes to organizational buying behavior literature by examining coopetition from a multilevel perspective. From a managerial perspective, the findings establish the importance of recognizing individual-, and organizational-level activities. Highlights: The paper contributes to organizational buying behavior research by focusing on coopetition. Organizational buying behavior in coopetition occurs on individual, organizational, and relational levels. Interrelated cooperative and competitive activities on multiple levels shape organizational buying behavior over time.